Comment on “Influence of traditional Chinese thought on the performance style and creation of piano music works” - Yusen Feng (Trans/Form/Ação)
Commented article: LI, N.; CHEN, Y. Influence of traditional Chinese thought on the performance style and creation of piano music works. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 5, p. e02400155, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15088.